OPTIMAL OFFSHORE PIPELINE CORRIDOR AND ROUTE SELECTION USING SPATIAL DECISION SUPPORT SYSTEM (SDSS) - BALOGUN, ABDUL-LATEEF (2014)
The merits of Geographic Information System (GIS) as an effective and versatile analytical tool have enhanced its acceptability as a route selection tool for oil and gas pipelines. Consequently more operators are utilizing the technique, especially for onshore pipeline routing projects. With attention and activities rapidly expanding from onshore to offshore and ultradeep water oil exploration and transportation, it is pertinent to extend the GIS spatial decision making procedure to the offshore domain. The study of offshore pipeline corridor and route selection using GIS and/or Spatial Decision Support System (SDSS) is a relatively new research field. This contrasts sharply with the use of GIS in onshore routing projects which have several case study reports in the literature.